Status of Marek's disease virus in established lymphoma cell lines: herpesvirus integration is common. - Delecluse, H J (1993)
Six cell lines derived from Marek's disease lymphomas of chickens and turkeys were investigated for the status of Marek's disease virus (MDV) DNA. In the transformed T- and B-cell lines, viral DNA could be detected by conventional Southern blot hybridization, by Gardella gel electrophoresis, and by in situ hybridization of metaphase and interphase chromosomes. Integration of viral DNA into the host cell chromosome was observed in all cell lines. Two to 12 integration sites of viral DNA could be detected in metaphase chromosome spreads. The integration sites were characteristic for the individual cell lines and were preferentially located at the telomers of large- and mid-sized chromosomes or on minichromosomes. In four of six cell lines, a minor population of latently infected cells supported the lytic cycle of MDV, giving rise to linear virion DNAs. In one of these cell lines, a third species of MDV DNA could be detected with properties reminiscent of covalently closed circular DNA. The finding that MDV integrates regularly into the genomes of latently infected cells is crucial to understanding the molecular biology of herpesvirus-induced tumors in the natural host.